The effects of odor and body posture on perceived duration - Schreuder, Eliane; Hoeksma, Marco R.; Smeets, Monique A.; Semin, Gün R. (Frontiers in Neurorobotics, 2014)
This study reports an examination of the internal clock model, according to which subjective time duration is influenced by attention and arousal state. In a time production task, we examine the hypothesis that an arousing odour and an upright body posture affect perceived duration. The experimental task was performed while participants were exposed to an odour and either sitting upright (arousing condition) or lying down in a relaxing chair (relaxing condition). They were allocated to one of three experimental odour conditions: rosemary (arousing condition), peppermint (relaxing condition) and no odour (control condition). The predicted effects of the odours were not borne out by the results. Self-reported arousal and pleasure states were measured before, during (after each body posture condition) and post experimentally. Heart rate and skin conductance were measured before and during the experiment. As expected, odour had an effect on perceived duration. When participants were exposed to rosemary odour, they produced significantly shorter time intervals than in the no odour condition. This effect, however, could not be explained by increased arousal. There was no effect of body posture on perceived duration, even though body posture did induce arousal. The results do not support the proposed arousal mechanism of the internal clock model.